Ocorrência e conservação de Touit melanonotus (Aves, Psittacidae) no sul do Brasil - Vallejos, Marcelo A. V.; Belmonte-Lopes, Ricardo; Klemann-Junior, Louri; Bornschein, Marcos R.; Deconto, Leonardo R.; Carrano, Eduardo [UNESP]; Gussoni, Carlos O. A. [UNESP] (Fundação Zoobotânica do Rio Grande do Sul, 2013)
O apuim-de-costas-pretas [Touit melanonotus (Wied, 1820)] é uma espécie florestal endêmica da Mata Atlântica Brasileira e de relevante interesse conservacionista. Trata-se de uma ave com poucas informações disponíveis acerca de sua história natural e distribuição geográfica e novas observações são importantes fontes de informação para auxiliar na conservação da espécie. Aqui reavaliamos o primeiro registro da espécie e apresentamos novas observações no estado do Paraná, sul do Brasil. As vocalizações atribuídas a T. melanonotus e que consubstanciaram sua ocorrência no estado foram examinadas com auxílio de espectrogramas e identificadas como vozes de Pionopsitta pileata (Scopoli, 1769). Não obstante, T. melanonotus ocorre com certa regularidade no Paraná, como indicado por novos registros da espécie em sete localidades distribuídas por todo o litoral do estado. Esta ave foi registrada principalmente em florestas de terras baixas e, uma vez que esta fisionomia sofre intensas pressões antrópicas, sugerimos que esforços de conservação da espécie devem priorizar a preservação desses hábitats.

The Brown-backed Parrotlet [Touit melanonotus (Wied, 1820)] is a rare forest species restricted to the Brazilian Atlantic Forest, and is included in the endangered category for species threatened of extinction. As there is a lack of knowledge about the species' natural history and occurrence, new observations can provide helpful information for parrotlet conservation. Here we reevaluate the first record for the species and present new records for the state of Paraná (southern Brazil). The vocalizations previously attributed to T. melanonotus, and which were used to infer its occurrence in the state, were examined by spectrogram analysis. These were actually found to be vocalizations of the Red-capped Parrot [Pionopsita pileata (Scopoli, 1769)], representing a case of misidentification. Even so, the Brown-backed Parrotlet occurs with some regularity in the state of Paraná, as shown by 12 records spread through seven localities spanning the entire Paraná coast. The Brown-backed Parrotlet was recorded mostly in lowland areas, and as these forest types suffer intense pressures, conservation efforts aiming the species preservation should focus in the maintenance of these habitats.
Occurrence and conservation of Touit melanonotus (Aves, Psittacidae) in southern Brazil
Keywords: Apuim-de-costas-pretas; floresta litorânea; litoral do Paraná; vocalização; Brown-backed Parrotlet; lowland forests; Paraná coast; vocalization